Being critical about resourcing. (2nd January 2023) - Caswell, Jo; Peach, Kate
Abstract : Resourcing in early years is a debatable subject, from neutral colours to food play. Consultants Jo Caswell and Kate Peach give insight into both their own practice as well as their work with early years settings across the UK around this subject. They urge us to be reflective and critical when it comes to resourcing our provision.